The utility and acceptability of a Brass V-drape versus a Maternawell tray for the collection of postpartum blood loss in low-risk term vaginal deliveries: a prospective parallel randomized trial - Esau, Jade Monique; Morris, T; Muller, CJB (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMEd)--Stellenbosch University, 2023.